THE IMPACT OF ONLINE FEEDBACK ON SELF-CONFIDENCE IN ENGLISH COMMUNICATION IN THAI SECONDARY SCHOOL STUDENTS - Srisuk, Nattamon; Songkram, Noawanit; Tantrarungroj, Pornsook; Thamsuwan, Pattarporn; Songkram, Nutthakorn (Journal of Education and Innovation, 2024)
EEnglish communicative skills are an essential part of learning and teaching English as a foreign language (Bao & Thang; Cárdenas-Claros, 2020; Clément et al., 2001; Gibbs & Simpson, 2005). Thai students struggle to learn English then leads to low self-confidence which affects their English. These negative emotions can impact learning and self-esteem (Pattanpichet, 2011; Schwartz & White, 2000; Trimmer & Guest, 2020). The goal of this paper is to look at how online personalized feedback affects students' self-confidence in English communication. A survey of secondary school students in Bangkok, Thailand, was conducted for this study. There are 346 available sample participants. Structural Equation Modeling (SEM) is used to evaluate the relationship between Personalized Feedback (PF), Feed Forward (FF), and Self-confidence in English Communication (EC). The causal equation model was examined, and the findings showed that the direct effect of PF on EC was 0.37, while the indirect effect of PF on EC was 0.47. According to the findings of this study, there is a positive relationship between personalized feedback and academic self-confidence in English communication.